2018: A watershed year for psychedelic science. (August 2019) - Aday, Jacob S; Davoli, Christopher C; Bloesch, Emily K
While interest in the study of psychedelic drugs has increased over much of the last decade, in this article, we argue that 2018 marked the true turning point for the field. Substantive advances in the scientific, public, and regulatory communities in 2018 significantly elevated the status and long-term outlook of psychedelic science, particularly in the United States. Advances in the scientific community can be attributed to impactful research applications of psychedelics as well as acknowledgement in preeminent journals. In the public sphere, Michael Pollan's book How to Change Your Mind was a commercial hit and spurred thought-provoking, positive media coverage on psychedelics. Unprecedented psychedelic ballot initiatives in the United States were representative of changes in public interest. Finally, regulatory bodies began to acknowledge psychedelic science in earnest in 2018, as evidenced by the designation of psilocybin-assisted psychotherapy to "breakthrough therapy" status for treatment-resistant depression by the U.S. Food and Drug Administration (FDA). In short, 2018 was a seminal year for psychedelic science.